Motivasi Kerja dan Kemampuan Manajerial Kepala Sekolah dalam Meningkatkan Mutu Lulusan - Qomaruddin Hidayat (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
This study aims to describe the motivation and managerial ability of the principal in improving the quality of graduates at SMK Muara Ilmu Bojongsari Depok. This research is a case study research model. Data collection is carried out by means of observation, interviews, and documentation. In observation activities, the researcher in this case acts as a passive observer participant, interviews are conducted to dig up information from the principal, vice principal for curriculum, teachers, and students. The data obtained is then analyzed by means of data reduction, display data, and conclusion making. The results of this study are presented in the form of a descriptive narrative equipped with images and tables. From the results of the research obtained, the motivation and managerial ability of the principal play an important role in the success or failure of the quality of graduates produced by an educational institution. Handling school management that is not balanced by good motivation and managerial ability from the principal as the head of an educational institution will have an impact on the quality results of graduates that are not optimal.